Relative sensitivities of common freshwater fish and invertebrates to acute hypoxia - Michael J. Landman; Michael R. Van Den Heuvel; Nicholas Ling (New Zealand Journal of Marine and Freshwater Research, 2005)
The acute lethality of low dissolved oxygen (DO) was examined in laboratory studies using several New Zealand freshwater fish and two invertebrates at 15°C. The 48‐h LC50 value was used as the endpoint for acute DO sensitivity as, owing to rapid mortality, this was found to best approximate the threshold lethal concentration. Median lethal time to death did not provide a reliable endpoint for comparing sensitivities. Fish LC 50 values varied from 0.54 to 2.65 mg litre ‐1 , with inanga whitebait (Galaxias maculatus; 2.65 ± 0.19 mg litre ‐1 , mean + SEM) being the most sensitive species tested. Common smelt (Retropinna retropinna; 1.83 ± 0.08 mg litre –1 ) and rainbow trout (Oncorhynchus mykiss; 1.61 ± 0.06 mg litre –1 ) were similar in their sensitivities, whereas common bully (Gobiomorphus cotidianus; 0.91 ± 0.06 mg litre –1 ) and shortfin eel elvers (Anguilla australis; 0.54 ± 0.03 mg litre –1 ) were the most tolerant fish. The shrimp (Paratya curvirostris; 0.82 ± 0.09 mg litre –1 ) and freshwater crayfish (Koura, Paranephrops planifrons; 0.77 ± 0.06 mg litre –1 ) were also tolerant to low DO. A subset of experiments to determine the relative sensitivities of larval and juvenile trout and bully indicated no significant differences between these life stages.